2018
DOI: 10.1155/2018/3076986
|View full text |Cite
|
Sign up to set email alerts
|

Adult Gross Motor Learning and Sleep: Is There a Mutual Benefit?

Abstract: Posttraining consolidation, also known as offline learning, refers to neuroplastic processes and systemic reorganization by which newly acquired skills are converted from an initially transient state into a more permanent state. An extensive amount of research on cognitive and fine motor tasks has shown that sleep is able to enhance these processes, resulting in more stable declarative and procedural memory traces. On the other hand, limited evidence exists concerning the relationship between sleep and learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 133 publications
2
19
0
Order By: Relevance
“…This hypothesis is supported by studies demonstrating that gross motor learning (such as whole-body postural tasks) may need extensive training to reach asymptotic performance. 3,40 Overall, our findings reinforce the current idea that explicit sequential knowledge is not sufficient to trigger sleep-dependent consolidation processes. 2 The level of complexity of the motor learning, as well as retesting at 24 hours, should be further explored in future investigations using complex motor paradigms.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This hypothesis is supported by studies demonstrating that gross motor learning (such as whole-body postural tasks) may need extensive training to reach asymptotic performance. 3,40 Overall, our findings reinforce the current idea that explicit sequential knowledge is not sufficient to trigger sleep-dependent consolidation processes. 2 The level of complexity of the motor learning, as well as retesting at 24 hours, should be further explored in future investigations using complex motor paradigms.…”
Section: Discussionsupporting
confidence: 87%
“…2 Contrasting with this extensive literature on SFTTs, only a few studies have been devoted to exploring the acquisition and consolidation effects in sequential gross movements and even fewer when the lower limbs were involved. 3 This lack in the motor learning literature is surprising, as many of our daily activities require sequential lower-limb movements, and these become even more important in both sport and clinical contexts (eg, functional rehabilitation). Therefore, there is a crucial need to examine whether findings from SFTTs may be generalized to other sequential gross motor tasks using different effectors and closer to an ecological context.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are more studies about the role of sleep in motor ability and motor learning [12,22] at any age of life [22,23]. Particularly, an interesting report of Bothe et al [22] in 2018 showed the impact of sleep on gross motor adaptation in a group of adolescents with typical developing profile, pinpointing the role of an increase in REM sleep on cortico-cerebellar network activity that organizes dynamic aspects of movement such as motor coordination.…”
Section: Discussionmentioning
confidence: 99%